2023
DOI: 10.1002/hsr2.1175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum interleukin‐1 receptor antagonist levels in major depressive disorder: A case‐control study

Abstract: Background and Aims Major depressive disorder (MDD) is characterized by the occurrence of one or more depressive episodes lasting a minimum of 2 weeks and is marked by a persistently low mood and a lack of enjoyment in daily activities. The diagnosis of MDD is not possible by a well‐established laboratory test or biomarker. A wide range of potential biomarkers for depression have been proposed by many studies, but none of them has adequately described the correlation between the biomarkers and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Measuring the serum leptin and EGF levels alone cannot accurately represent the entire neuroinflammatory process of major depressive disorder. It would help to understand the pathophysiology of MDD more accurately when measuring other parameters in the same demographic and laboratory settings [ 53 , 54 ]. Moreover, the duration of depression, that could potentially influence the levels of inflammatory parameters was not considered.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the serum leptin and EGF levels alone cannot accurately represent the entire neuroinflammatory process of major depressive disorder. It would help to understand the pathophysiology of MDD more accurately when measuring other parameters in the same demographic and laboratory settings [ 53 , 54 ]. Moreover, the duration of depression, that could potentially influence the levels of inflammatory parameters was not considered.…”
Section: Discussionmentioning
confidence: 99%
“… 35 In consistent with some earlier studies, we observed sex-specific differences for serum MIF levels among patients. 49 - 52 A few studies reported decreased and elevated MIF levels in MDD individuals. 47 , 48 According to the present study findings and previous results, serum MIF levels are inconsistent among the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory pathway mediates a connection between sickness behavior and clinical depression. 45 Rodent studies reported that the administration of pro-inflammatory cytokines induced depressive-like behaviors suggesting the association between depression and inflammation. 46 Elevated IL-2 levels cause the degradation of the tryptophan (TRP) enzyme, a precursor of serotonin production through the IDO pathway, and thereby lead to depression.…”
Section: Introductionmentioning
confidence: 99%